SOSIALISASI PROKES PTM (PEMBELAJARAN TATAP MUKA) DI MASA PANDEMI COVID 19 DALAM RANGKA PTM TERBATAS DI ITKES MUHAMMADIYAH SIDRAP - Hamdiyah; Rosmawaty; Ariyana; Syamsa Latief (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Corona Virus Disease 2019 is a new type of disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) or commonly known as the novel coronavirus (2019-nCoV). Covid 19 has had a major impact because of this corona virus, various policies have been issued by the government. The government's efforts will be successful if we as a society obey the policies that have been made, however, many of the people underestimate this Covid-19 because they think that this virus has the same symptoms as the common cold which will heal by itself. Even some people are still carrying out activities outside without wearing masks and implementing social distancing or keeping a distance from others and have not gotten used to washing hands with soap to reduce the risk of being exposed to the corona virus. This condition underlies me to do service that aims to reduce the chain of spread of Covid-19 in the community. Efforts to prevent the corona virus have many ways, such as applying a healthy living culture. Healthy living culture itself is something that must be applied in life. According to Kotler, a healthy lifestyle is a description of our activities or activities that are supported by our desires and interests and how our minds live them in interacting with our environment (Department of Health, n.d.). Providing assistance to the community regarding the importance of a healthy lifestyle is important during a pandemic like today. Assistance with healthy lifestyles can be done through online and offline media. With this assistance, it is hoped that the community will understand and know how to avoid the corona virus.